Determinants of Intention to Forward Online Company-generated Content via Facebook - Mahmoud Yasin; LucÃa Porcu; Francisco LiÃ©bana-Cabanillas (International Review of Management and Marketing, 2019)
The aim of the present study is to analyze consumer intention to forward online company-generated content (CGC) from the retail banking sector via Facebook, the leading social network, based on a) the mediating effect of attitude to forwarding online CGC on the relationship between brand experience and the intention to forward online CGC and b) the mediating effect of Facebook perceived usefulness on the influence of subjective norms and source trustworthiness on the intention to forward online CGC. A sample of 404 users was recruited, and data collected by means of questionnaires distributed via email and personal interviews. The dataset obtained was analyzed using Structural Equation Modeling. The findings demonstrate the mediating effect of attitude as the main antecedent of intention to forward online CGC. Relevant scholarly and managerial implications are drawn for financial entities and the agencies that provide them with corporate and marketing communications services.